Electrochemical detection of folic acid using a modified screen printed electrode - Sayed Zia Mohammadi; Farideh Mousazadeh; Maryam Mohammadhasani-Pour (Journal of Electrochemical Science and Engineering, 2022)
In this work, an electrochemical sensor was established for the detection of folic acid based on Ni-BTC (BTC = benzene-1,3,5-tricarboxylic acid) metal-organic framework (MOF) modified screen-printed electrode (SPE). Electrochemical techniques (cyclic voltammetry (CV), differential pulse voltammetry (DPV), linear sweep voltammetry (LSV) and chronoamperemetry (CHA) were used for the detection of folic acid at Ni-BTC MOF modified SPE. The results indicate that the as-prepared sensor has a good electrocatalytic effect on the detection of folic acid. This electrochemical sensor showed a dynamic linear response range from 0.08 to 635.0 µM and the detection limit was estimated to be 0.03±0.001 µM. Moreover, the feasibility of Ni-BTC MOF/SPE sensor to detect folic acid in real samples was also evaluated by the standard addition method.